Expository Methods of Bundles HAP Affected the Implementation of HAP Prevention of Adult Inpatient Unit - Lia Pratiwi; Yosi Maria Wijaya; Monica Saptiningsih (Journal of Ners and Midwifery, 2022)
Hospital-acquired pneumonia (HAP) incidents in private hospitals in Bandung reached 0.11 % -1.03 %. HAP affects the quality of hospital services related to patient safety. One of the methods used for socializing implementation of HAP prevention was the expository method means learning method that is directly implemented to maintain contact between the speaker and audience. The purpose of this study was to determine the effect of the expository method of education on HAP bundles on the implementation of HAP prevention in the adult inpatient units. The study was designed by pre-experimental design one group pretest-posttest. A total of 16 associate nurses were part of the research using the purposive sampling technique in the adult inpatient units. The variable in the study was the implementation of HAP prevention which was measured by using an observation sheet. Wilcoxon tests were used to compare the scores between pretest-posttest. The researched result was P-value 0.000 (P-value < Î± 0.05), meaning the expository method of education on HAP bundle affected the implementation of HAP prevention in the adult inpatient unit. Suggestions derived from this study are to advise the infection prevention and control committee to implement the expository method in socializing bundles to prevent infections categorized as HAIs to health workers and to perform a regular evaluation.